2020
DOI: 10.1021/acs.est.0c04279
|View full text |Cite
|
Sign up to set email alerts
|

Designing Materials for Aqueous Catalysis: Ionic Liquid Gel and Silica Sphere Entrapped Iron-TAML Catalysts for Oxidative Degradation of Dyes

Abstract: Materials have been developed that encapsulate a homogeneous catalyst and enable it to operate as a heterogeneous catalyst in water. A hydrophobic ionic liquid within the material was used to dissolve Fe-TAML and keep it from leaching into the aqueous phase. One-pot processes were used to entrap Fe-TAML in basic ionic liquid gels, and ionic liquid gel spheres structured via a modified Stöber synthesis forming SiO2 particles of uniform size. Catalytic activity was demonstrated via the oxidative degradation of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…It has been shown that entrapping Fe-TAML into liquid gels and silica spheres can reduce the deactivation of the Fe-TAML catalyst. 26 Abatement of Organic Compounds. The evolution of the concentrations of the selected organic compounds (i.e., micropollutant) was determined in the selected secondary wastewater effluent in the presence of Fe-TAML/H 2 O 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that entrapping Fe-TAML into liquid gels and silica spheres can reduce the deactivation of the Fe-TAML catalyst. 26 Abatement of Organic Compounds. The evolution of the concentrations of the selected organic compounds (i.e., micropollutant) was determined in the selected secondary wastewater effluent in the presence of Fe-TAML/H 2 O 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These results also roughly agree with the evolution of oxygen that was observed in Figure where the reaction slows down after about 10 min. It has been shown that entrapping Fe-TAML into liquid gels and silica spheres can reduce the deactivation of the Fe-TAML catalyst …”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition to ionic liquid gels containing Fe-TAML (4.2.1), McNeice et al prepared Fe-TAML ionic liquid silica spheres using a modified Stöber process. 115 This was the first report of ionic liquid silica sphere formation catalysed by the ionic liquid (without additional acid or base). In a one-pot mixture, water, silica precursors, Fe-TAML, and an aqueous solution of tetrapropylammonium hydroxide ([N 3 Upon addition of acetone, orange spheres were precipitated which contained Fe-TAML and ionic liquid.…”
Section: Water Remediationmentioning
confidence: 97%
“…McNeice et al built upon the basic ionic gel process described above 103,111 to incorporate Fe-TAML, a biomimetic peroxide activator, 114 within a basic ionic liquid gel for water purification (Figure 26). 115 These soft basic materials provided a protective environment and a more optimum pH for Fe-TAML operation. In the presence of H 2 O 2 the materials acted as a heterogeneous catalyst for the oxidation of dyes in aqueous solution.…”
Section: Water Remediationmentioning
confidence: 99%
“…14) is that, by tuning the solubility of the IL, the passage of chemicals into and out of the gel can be controlled, in order to protect the catalyst from harsh reaction conditions. 197 The ionic liquid keeps the enzyme in a liquid environment that promotes the right protein conformation for catalytic activity. 63,161,162,196 Enzyme entrapment in an IL gel can thus act to encapsulate and store enzymes in their active form.…”
Section: Hybrid Materialsmentioning
confidence: 99%